Land Use and Aquatic Invasive Species: Relationships in Southeastern Wisconsin Lakes - Pichler, Marie C. (My University, 2013)
Submerged aquatic vegetation provides many ecological services to waterways, including water quality control, erosion control, and habitat for small fish and invertebrates. When an exotic species is introduced, it can alter the services that native vegetation provides by growing densely. This invasive aquatic vegetation is managed in several different ways; such as cutting, pulling, herbicides, and biological control. Since these species spend their entire lives underwater, they are impacted by the water quality and nutrients in their waterway. Controlling nutrient influxes to waterbodies could theoretically be another management technique for invasive aquatic vegetation. In this study, densities of invasive plants within lakes were compared to the amount and spatial relationships of land use within the lake's sub-watershed. Low densities of invasive plants were correlated with high percentages and nearness of natural areas; except for forested areas, which had an inverse relationship. These results suggest that implementing natural buffers could potentially reduce populations of aquatic invasive plants.
Includes Tables, Figures, Maps and Bibliography.
Keywords: Land use; Southeastern Wisconsin; Lakes; Invasive species